Simulation of search-and-rescue and target surrounding algorithm techniques using Kilobots - Magsino, Elmer R. (Animo Repository, 2016)
This research study presents the simulation results, from the V-REP software, of using Kilobots in executing collective behaviors usually done in military operations. A given base configuration of 10 Kilobots are used in simulating both the target-surrounding and search-and-rescue behaviors. In each algorithm, a Kilobot performs three basic roles: (1) searcher/walker, (2) target and (3) base. In the target-surround behavior, a successful run is considered when five Kilobots have already encircled its target. In the search-and-rescue algorithm, three different techniques are presented, namely: (1) square formation, (2) dispersal and (3) sweep. Simulation results provide promising results for the hardware implementation of these proposed swarm behavior techniques though it will be seen the limitations of the V-REP software. © 2016 IEEE.